The features of proliferative processes in the thyroid gland of the wistar rat’s offspring after intrauterine action of dexamethasone - Fedosieieva, O. V.; Федосеева, О. В.; Федосєєва, Ольга Віталіївна (Харків : Харків. нац. мед. ун-т, 2020)
The features of proliferative processes in the thyroid gland of the Wistar rat’s offspring after intrauterine action of dexamethasone were studied. Animals were divided into 3 groups: I – intact rats; II – control – animals, which on the 18th day of the dated pregnancy transuterine, transdermal, subcutaneously in the interscapular area was injected with 0.9 % saline in the amount of 0.05 ml; III – experimental group – animals, which during laparotomy by intrauterine, transdermal subcutaneous injection in the interscapular area was injected with a solution of dexamethasone at a dose of 0.05 ml at a dilution of 1:40 intrauterinely on the 18th day of pregnancy (Ukrainian patent ¹ 112288). In the experimental subgroups used the allowable, generally accepted number of animals for statistical processing and obtaining reliable results – 6 animals. The thyroid gland with the tracheal area was removed on the 21st, 30th, 45th, 60th, 90th, 120th days of life. Immunohistochemical study was performed according to the protocol recommended for a particular antibody manufacturer. Monoclonal antibodies ki-67 (Ki-67), Fox-1 Antibody (A-12) were used to assess proliferative activity, the company Santa Cruz Biotechnology, Inc. (USA). The study found that the thyroid gland of rats of infantile period, which prenatally exposed to dexamethasone, is structurally represented by chaotically located follicles of different diameters with a predominance of large with desquamated cells in the lumen, and proliferative changes aimed at forming extrafollicular which is confirmed immunohistochemically by the presence of Ki-67-positive cells. Intracellularly, proteinsynthesizing organelles of thyrocytes also proliferate, to which there is a clear cytoplasmic and nuclear reaction with Fox-1 antibodies. During the juvenile period, proliferative processes in the thyroid gland of animals of the experimental group are stabilized while maintaining the morphological structure of the hypofunctional type, and remain lower compared to the control and intact groups. Morphological signs of functional tension of the thyroid gland animals exposed prenatally to dexamethasone, which correlate with a decrease in proliferative activity, indicate a functional compensatory response of synthetic and hormone-producing function, but suppression of proliferative processes, despite the slight manifestations. The thyroid gland of morphological hypofunctional type after prenatal action of dexamethasone in young rats, indicates an adaptogenic compensatory response and morphofunctional immaturity of the organ during this period, which may be the basis for provoking the preservation of such morphogenetic factors under the influence of stressors.
Особенности пролиферативных процессов в щитовидной железе потомков крыс линии Вистар после внутриутробного воздействия дексаметазона
Особливості проліферативних процесів у щитоподібній залозі нащадків щурів лінії Вістар після внутрішньоутробного впливу дексаметазону
https://orcid.org/0000-0003-2247-1965.
Keywords: thyroid gland; proliferation; dexamethasone; experiment; rats; щитовидная железа; пролиферация; дексаметазон; эксперимент; крысы; щитоподібна залоза; проліферація; експеримент; щури